(untitled) (Raparin Journal of Humanities (RJH), 2025)
The Hurrians were one of the oldest nations in Kurdistan and the ancient Near East. They had a highly developed civilization and their influence stretched over a vast area. The religious dimension of the Hurrians form a basic element in understanding these people. In this study research has been made of their religious beliefs in general and the Hurrian pantheon in particular. Details on the Hurrian pantheon are presented and an analysis of the structure of the Hurrian religious system has been done. Investigations have been done of the distinctive features of the pantheon deities. At the same time, the importance of mythology has been clarified in understanding the Hurrian pantheon. The introduction of the study serves as a gateway to the history of the Hurrian beliefs. In the conclusion of the research the most important findings are presented. The foundation and framework of the study is built around the analysis of the Hurrians religious belief and their pantheon. As mentioned earlier the Hurrians are considered as one of the oldest and most influential nations in Kurdistan which have several hidden aspects, yet academic centers in Kurdistan have not done enough research in their history and archelogy. This attempt is a contribution to shedding light on one aspect of the importance of the history of this ancient nation. The Hurrian beliefs and pantheon make the most attractive dimension of these people’s civilization which is so complex and detailed has become a subject of discussion among academic centers.